2006
DOI: 10.1097/01.icu.0000193106.00089.a7
|View full text |Cite
|
Sign up to set email alerts
|

Update on utilities and cost–utility analyses

Abstract: Utilities are being used increasingly to measure health-related quality of life. Cost-utility analyses are becoming more readily available for comparing the incremental cost-effectiveness of different ophthalmic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Two similar reviews have been conducted to identify articles reporting utility values in patients with wAMD. One systematic review, published in 2006, identified utility and cost-utility articles in the area of wAMD, dry AMD, and diabetic retinopathy 22 . However, this review was very narrow in its scope, focusing only on articles published between January 2004 and January 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Two similar reviews have been conducted to identify articles reporting utility values in patients with wAMD. One systematic review, published in 2006, identified utility and cost-utility articles in the area of wAMD, dry AMD, and diabetic retinopathy 22 . However, this review was very narrow in its scope, focusing only on articles published between January 2004 and January 2006.…”
Section: Discussionmentioning
confidence: 99%